Scientific foundations of intra-industry foreign trade - SODIKOV Zokir Rustamovich (Peerian Journals Publishing, 2025)
The article analyzes the new dimensions of international trade and its development trends. In this regard, the scientific foundations of this process are explained through the theories of monopolistic competition and economies of scale. While classical trade theories scientifically justify the economic processes between developing countries and industrialized nations, the new theories of monopolistic competition and economies of scale highlight the causes and factors driving the intensification of trade among developed countries. In particular, the priority influence of product discrimination and production diversification in this process is emphasized.
Keywords: monopolistic competition; economies of scale; foreign trade